Presurgical nasoalveolar molding in a patient with left unilateral cleft lip and palate - Rodríguez-Solano, María Paulina; Vergara-Mercado, Martha Ligia (Universidad y Salud, 2020)
Introduction: Cleft lip and palate is a craniofacial birth defect that accounts for 1:1000 live birhts in Colombia. Performing nasoalveolar molding before surgery facilitates the reshaping of deformed nasal cartilage and alveolar processes. Objective: To make professionals aware of the importance of performing nasoalveolar molding in a patient with cleft lip and palate before surgical intervention. Materials and methods: A 17-day-old infant with a full left unilateral cleft lip and palate was treated at the dental clinic of the University of Sinú, Montería (Córdoba, Colombia). Once the dental clinical history was recorded, an orthosis plate was made. The plate was changed every 15 days and the molding appliance was repositioned every 8 days. Results: The orthosis plate promoted nasoalveolar molding, which facilitated feeding and improved the shape of nasal tissues. Consequently, this early intervention improved the preparation for the surgery of the cleft when the child reached 8 months of age. Conclusions: Nasoalveolar molding in patients with full cleft lip and palate is important to promote better physical conditions, which favor food intake and benefit their physical appearance.